Molecular species delimitation of the genera Anodus, Argonectes, Bivibranchia and Micromischodus (Ostariophysi: Characiformes) - Nogueira, Acacio Freitas [UNESP] (2021)
A good taxonomic assessment of specimens is an essential task to many biological studies and DNA data have provided additional sources of information to assist in the disentanglement of taxonomic problems among living organisms, as has been the case of some taxa of the megadiverse Neotropical ichthyofauna. Here we assessed all valid species in the Neotropical freshwater fish genera Anodus, Argonectes, Bivibranchia and Micromischodus of the family Hemiodontidae to establish molecular species boundaries among them. All species delimitation methods defined exactly only one MOTU for Anodus elongatus, Argonectes longiceps, A. robertsi, Bivibranchia bimaculata, B. notata, B. velox, and Micromischodus sugillatus, resulting in total congruence between nominal species and MOTUs for these seven taxa. The three species having discordant results across analyses: Anodus orinocensis, Bivibranchia fowleri, and Bivibranchia simulata, matched more than one MOTU per species in some methods, meaning that cryptic diversity may exist within these taxa. Overall, this great correspondence among morphological and molecular boundaries for thae species analysed seem to be indicative of a reasonably stable taxonomy within these Hemiodontidae genera.